PENERAPAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) PADA PEMILIHAN SUPPLIER DI PERUSAHAAN XYZ - I Komang Jara Sanda, Anak Agung Istri Agung Sri Komaladewi, Ni Made Cyntia Utami, I Gusti Agung Kade (JURNAL RISET DAN APLIKASI TEKNIK INDUSTRI, 2023)
Company XYZ is a company in the field of chicken breeders. So far, the company has never applied a method in selecting suppliers. The company is not satisfied with the current suppliers. The company owner wants to evaluate the selection of animal feed suppliers to find out the right supplier to be chosen by the company according to the company's criteria. The company uses price, service, quality, and delivery criteria as elements in choosing animal feed suppliers. The Analytical Hierarchy Process (AHP) method is used to solve this problem. The Analytical Hierarchy Process (AHP) method starts from identifying problems or goals. After that, a paired comparison of each element of comparison is carried out to obtain the priority level of each element, then consistency testing is carried out to ensure that the comparison is consistent. Alternatives that become animal feed suppliers in accordance with the criteria of Company XYZ are Supplier C (0.4465) being alternative I, Supplier B (0.2798) being alternative II, and Supplier A (0.2737) being alternative III. These results can be input for the company to choose the supplier to be used